Combining Written Discourse Analysis with the Teaching of Second Language Writing - Hennach, Aboud; Nemouchi, Abdelhak (Journal of Human Sciences, 2020)
The ever-increasing technological development along with the ever-decreasing distance between nations, cultures, and communities place writing at the top of the skills pyramid. Along with its social, communicative, and economic benefits, writing is an essential component of success within the educational enterprise and in language apprenticeship, more precisely. This paper looks at the practicality and possibility of applying written discourse analysis to the teaching of L2 writing for Second Year L.M.D students. A discourse-oriented paradigm of teaching writing uses written discourse analysis as a method of instruction which would raise the students’ awareness of the text and discourse patterns and develop their abilities of topic introductions, smooth shifts, persuasion devices, and their lexico-syntactic means of establishing cohesion.